DOI: 10.5463/thesis.72
|View full text |Cite
|
Sign up to set email alerts
|

Context is Key

Abstract: Western European countries have seen a major rise in the diversity of their population over the past few decades. At the same time, the ideas of tolerance, acceptance and respect which provided the main components of multiculturalism in the 1990s have been challenged by increasing polarization within society, with immigration representing a topic of heated debates. Despite decreasing (youth) crime rates, immigration is often linked to crime in these debates, and more particularly the overrepresentation in crim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 103 publications
0
5
0
Order By: Relevance
“…Immunostaining of brain tissues for tau and αsyn antibodies has revealed a higher burden of α-syn pathology in AD with LBs (AD+LB) compared to PD dementia cases. Interestingly, the pathological tau load was found to be similar or even slightly lower in AD+LB compared to AD alone, with co-localization of phosphorylated tau and α-syn within astrocytes in the middle temporal gyrus [39]. In contrast, autopsy literature on PD frequently reports concurrent deposition of α-syn and tau, reflecting a complex interplay that may differ from AD pathology.…”
Section: Discussionmentioning
confidence: 93%
“…Immunostaining of brain tissues for tau and αsyn antibodies has revealed a higher burden of α-syn pathology in AD with LBs (AD+LB) compared to PD dementia cases. Interestingly, the pathological tau load was found to be similar or even slightly lower in AD+LB compared to AD alone, with co-localization of phosphorylated tau and α-syn within astrocytes in the middle temporal gyrus [39]. In contrast, autopsy literature on PD frequently reports concurrent deposition of α-syn and tau, reflecting a complex interplay that may differ from AD pathology.…”
Section: Discussionmentioning
confidence: 93%
“…Paid parental leave is important because it is implemented at such a critical point in the lifecourse -childbirth, and thus has the ability to influence parental behaviour 21 , and can drive attitudinal shifts 22 . In a recent survey of 12,000 people across 15 countries i it was found that 87 percent of mothers and 85 percent of fathers think that taking paid care leave will benefit both their partner and children 4 . ii This includes casual employees that have worked on a regular basis for the previous 12 months and that are expected to con:nue this work.…”
Section: 1mentioning
confidence: 99%
“…Overall, 56 percent of new fathers did not seek information or support from any source during stressful periods. However, it is reported that men who take care of their emotional selves are 2 to 8 times more likely to care for a family member 4 . Hence, we can see a positive correlation between men taking care of their mental health, and their engagement and capacity to provide care to others.…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations